Phases of Ptolemaic Roman 273-30BC - Abdullah, Hassan Togun; Hassan, Marwa Habib (Journal of Humanities & Social Sciences, 2020)
This research dealt with the development of Egypt’s Ptolemaic relations with Rome and took the appearance of its development and the increasing interest of the Romans in the affairs of Egypt. The Ptolemaic state and its fall in the hands of the Romans year 30 BC, represented by the State of Egypt on the continent of Africa and its borders extending from the Mediterranean Sea in the north to the Gulf of Suez and the Red Sea in the east and the deserts of Libya in the west and Nubia in the south and using the historical and analytical method based on linking historical events and facts with each other and analysis starting from a historical prelude is a presentation of the by collecting historical evidence and linking them together and presenting them correctly in their connotations which enabled the Romans to reach the goal of times the kingdoms of the East, including Egypt, so that they could conquer them by building Diplomatic relations during the early Ptolemaic era under the Treaty of Friendship between Rome and Egypt Over time, it turned into a policy of protection and then a policy of appointing and isolating the Ptolemaic kings, taking advantage of the conflict in the Ptolemaic House. The study recommends the need to study the urban side during that period as well as the cultural aspect.